Understanding designers’ switching intention to AI painting tools using the PPM framework - Yilin Liu; Ping Ji (Scientific Reports)
Abstract In recent years, the emergence of artificial intelligence painting tools has significantly changed the creative activities and future development of designers, but studies specifically addressing designers’ inclinations to transition to AI painting tools are scarce. Therefore, to understand designers’ switching intentions toward AI painting tools, this study proposed a research model based on the push–pull–mooring framework. Data were collected from 320 Chinese designers and analyzed using structural equation modeling. The results indicate that the attractiveness of AI painting tools is the main factor that affects the designers’ intentions to switch, followed by switching costs and dissatisfaction with traditional painting tools. Moreover, perceived pleasantness increased the attractiveness of AI painting tools, and individuals’ habits greatly improved switching costs. These results provided valuable empirical evidence for the future advancement of AI painting tools. The findings of this study not only provide light on the motivations behind designers’ decisions during periods of technological change but also offer valuable references for future technological directions in the design industry and the evolution of designers’ professional roles. Furthermore, it provides important recommendations for AI painting tool developers, emphasizing the need to enhance the tools’ creativity and appeal.